PAN – EUROPEAN TRANSPORT CORRIDORS IN THE POLICY OF THE EUROPEAN UNION - Mirosław CZECH (Scientific Journal of Silesian University of Technology. Series Transport)
The issue of organising efficient transport within Europe is one of the areas of a common policy of the European Union, shaped for over 30 years. Poland has been participating in this creative process since May 1, 2004. The intensity of the development of transport and the economy of individual countries that do not only belong to the Community but also have a significant impact on changes in the European Union's transport policy aimed at improving the course of pan-European transport corridors. In parallel with the creation of an effective European transport network, the rapid economic development of the regions belonging to the Union, including Poland, is becoming increasingly important. This article aims to discuss the issue of the development of the trans-European transport corridors, which also passes through the territory of Poland. In addition, this paper aims to present changes in EU policy concerning the shaping of transport infrastructure in Europe, following which a single transport network is to be created soon, meeting the communication and economic needs of the countries belonging to the Community.